The Indigenous McClain Doctrine: A New Legal Tool to Protect Cultural Patrimony and the Right to Self-Determination - Matthew H. Birkhold (Washington University Law Review, 2019)
In December 2010, the United States endorsed the United Nations Declaration on the Rights of Indigenous Peoples (UNDRIP), which obligates the United States to respect indigenous self-determination and protect Native American cultural objects. Yet, nearly a decade later, the United States has made little progress to meet these commitments, resulting in growing frustration in the indigenous and international human rights communities. At its 2017 meeting on the implementation of UNDRIP, the U.N. expert group condemned the United States for its inaction. But the failure to act is not the result of indifference. Current U.S. law makes it impossible for the United States to satisfy its human rights obligations. This Article identifies a paradoxical conflict resulting from the dual obligation imposed by UNDRIP: the current statutory scheme for protecting indigenous cultural property in America (NAGPRA) actually undermines tribal self-determination. By carefully analyzing NAGPRA case law, this article shows that non-indigenous judges, lawyers, and defendants identify what constitutes Native Americans’ cultural property. Tribal law represents the ideal legal scheme for respecting self-determination, but tribal criminal law cannot be extended over non-Indians, making it an ineffectual safeguard of cultural heritage. The seeming irreconcilability of these two goals amounts to the “indigenous cultural patrimony problem.” Can a law effectively protect Native American cultural patrimony while simultaneously respecting the right of indigenous peoples to exercise cultural self-determination? This article offers an innovative solution by applying art law jurisprudence to Federal Indian law. Specifically, this article argues that the paradox can be resolved by utilizing the legal instrument deployed to address stolen foreign cultural property (the McClain doctrine) in the domestic context. This Article proposes a new legal tool: the “indigenous McClain doctrine,” which effectively extends criminal tribal jurisdiction over non-Indians in cases involving stolen Native American cultural property, thereby resolving the conflict and meeting America’s obligations under UNDRIP. Importantly, this article demonstrates that the “indigenous McClain doctrine” faces no jurisprudential bar—despite the prohibition of extending tribal criminal law to non-Indians—and it makes recommendations on how to achieve its implementation.
Keywords: UNDRIP; Tribal law; Tribal self-determination; Cultural patrimony; McClain doctrine; Cultural property